If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + y = 3 Solving -5 + y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + y = 3 + 5 Combine like terms: -5 + 5 = 0 0 + y = 3 + 5 y = 3 + 5 Combine like terms: 3 + 5 = 8 y = 8 Simplifying y = 8
| 2x+4=3x+3 | | 4x=3x-9 | | 7-k=3 | | 3x-8=7x-40 | | 9y^2-4=0 | | y=0.42x+3 | | y=-0.28x-8 | | -12=k+24 | | 2k+5=25-5 | | -3.8+x=5.8 | | 6n^2+19n-7=0 | | -3.2=b+(-0.2) | | 6n+19n-7=0 | | z+=-13 | | a-14=18 | | m+8=14 | | m-1.2=-1.2 | | 50-k=80 | | 6x-9y=72 | | 3y^2-4=-4y | | 4(x+2)2-4=12 | | 2(x+7)=10 | | 9x^2+3kx-k=0 | | x^2-6x+3=k(2x-1) | | 15-5x=-25 | | 3x-9=42 | | 42-20=2p | | 3y^2-4=4y | | -4x-40-14x=32 | | C=Amt | | C=Amy | | x-x*0.2=y |